Subsequent Pregnancy Outcomes After Open Maternal-Fetal Surgery for Myelomeningocele. Issue 1 (March 2020) - Goodnight, W.H.; Bahtiyar, O.; Bennett, K.A.; Emery, S.P.; Lillegard, J.B.; Fisher, A.; Goldstein, R.; Jatres, J.; Lim, F.Y.; McCullough, L.; Moehrlen, U.; Moldenhauer, J.S.; et al.
Abstract : ( Am J Obstet Gynecol . 2019;220:494.e1–494.e7) Open maternal-fetal surgery (OMFS) for fetal myelomeningocele (fMMC) is associated with a significant reduction in morbidity related to spina bifida. OMFS for fMMC may be associated with adverse outcomes in subsequent pregnancies, but there are limited data available. There is a uterine rupture risk of 4% to 9% associated with a classical hysterotomy, but its unclear whether this risk is similar in hysterotomy for OMFS for fMMC. In 2012, the Fetal Myelomeningocele Consortium, now consisting of 25 institutions, was created to establish a registry of patients undergoing fMMC closure. This study aimed to investigate the maternal and neonatal outcomes in subsequent pregnancies following OMFS for fMMC closure.